Montessori and Contextual Teaching Learning Method for Beginning Reading Abilities: Metode Montessori dan Contextual Teaching Learning untuk Kemampuan Membaca Permulaan - Rakhmawati, Agustina Dewi; Chamidah, Atien Nur; Pujaningsih (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Beginning reading is a foundational stage in early literacy development, particularly for children with learning disabilities who require structured and meaningful learning experiences. Specific background: In Group B of Kindergarten 1 North Sangatta, several children showed difficulties recognizing letters, distinguishing similar symbols, connecting sounds to written forms, and maintaining interest in reading activities. Knowledge gap: Existing classroom practices had not yet integrated multisensory and contextual media that align with children’s developmental characteristics. Aim: This study examined the use of the Montessori method combined with Contextual Teaching and Learning to support beginning reading abilities through structured letter-card activities. Results: Conducted through two cycles of Classroom Action Research, the intervention increased student performance from 50% at baseline to 84% in Cycle I and 94% in Cycle II, surpassing the school’s mastery criteria. Children became able to identify at least twenty alphabet letters, differentiate similar letter pairs, and read simple contextual words. Novelty: The study presents an applied model that connects Montessori sensorial materials with contextual learning tasks, allowing children to link phonetic concepts to real-life experiences. Implications: This integrative approach can be used in daily classroom practice to strengthen beginning reading abilities in children with learning disabilities. Highlights The Montessori and contextual teaching learning method supported beginning reading abilities in children with learning disabilities. Letter-card activities facilitated recognition of alphabet forms and sounds in meaningful contexts. Classroom action cycles showed steady progress in reading indicators across both implementation stages. Keywords Beginning Reading, Learning Disabilities, Montessori Method, Contextual Teaching Learning, Letter Card Media